VARIASI GENETIK DAN IDENTIFIKASI Usnea spp. BERDASARKAN KARAKTER MORFOLOGIS DAN MOLEKULAR - , Miftahul Jannah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lichen is an outstanding successful group of symbiotic organisms, which comprise the strand of algae partner (phycobiont) and fungal partner (mycobiont). Lichen of the genus Usnea are used as a traditional herbal remedies. This genus has the thallus which is very similar among species, so it is very difficult to distinguish. Based on morphological character, identification of species in Indonesia is still limited. Morphological characters is can be used to identify in family and genus only. The molecular character based on Internal Transcribed Spacer (ITS) rDNA sequences which has conserved region (5.8S) and varied region (ITS1 and ITS2 ) is needed to strengthen and support the identification and phylogenetic analysis. The objective of this research was to identify and make phylogenetic analysis of Usnea species from the forest of Gunung Lawu (LW), Center Java and Turgo (T), Yogyakarta. Identification had been conducted based on morphological characters, anatomical, microchemistry, and microcrystals. ITS rDNA sequence was analyzed by Bioedit software, cutting of the sequence based on chromatogram was analyzed using DNA Baser, BLAST to determine the level of homology, sequences alignment samples was analyzed using Clustal-X, nucleotide similarity with Phydit and clustering (phylogeny tree reconstruction) was constructed with Maximum Likelihood (ML), the model of evolution Kimura-2 parameter with the bootstrap 1000 on MEGA-5.05. It was found 7 species from 16 of the morphotype based on morphological characters, U. pectinata (LW3), U. rubrotincta (LW4),U. himalayana (LW1, LW2, LW5, LW11), U. fragilescens (LW6, LW9), U. nidifica (LW8,LW10), U. baileyi (LW7,T1,T3), and U. bismolliuscula (T2,T4,T5), while based on ITS rDNA is identified only 6 species, U. pectinata and U. baileyi was identified as the same species, U. baileyi. Dendogram based on morphological character showed that U. pectinata was closely related to U. bismolliuscula, U. rubrotincta was closely related to U. fragilescens, U. himalayana was closely related to U. nidifica, and U. baileyi distantly related to Usnea was found. Topology of the phylogenetic based on ITS rDNA sequences showed that the clade of subgenus Usnea, U. himalayana was closely related to U. nidifica, U. bismolliuscula was more closely related to U. rubrotincta than U. fragilescens, and the clade of subgenus Eumitria, U. pectinata was closely related to U. baileyi. Key words: lichen, Usnea, ITS rDNA, morphological, phylogenetics